A disease‐specific quality of life instrument for non‐alcoholic fatty liver disease and non‐alcoholic steatohepatitis: CLDQ‐NAFLD. (13th March 2017) - Younossi, Zobair M.; Stepanova, Maria; Henry, Linda; Racila, Andrei; Lam, Brian; Pham, Huong T.; Hunt, Sharon
Abstract: Background: Non‐alcoholic fatty liver disease and non‐alcoholic steatohepatitis are the most common causes of chronic liver disease with known negative impact on patients' health‐related quality of life. Our aim was to validate a disease‐specific health‐related quality of life instrument useful for efficacy trials involving patients with non‐alcoholic fatty liver disease and non‐alcoholic steatohepatitis. Methods: From a long item selection questionnaire, we selected relevant items which, by factor analysis, were grouped into domains constituting Chronic Liver Disease Questionnaire—Non‐Alcoholic Fatty Liver Disease version. The developed instrument was subjected to internal validity, test‐retest reliability and construct validity assessment using standard methods. Results: For development of the Chronic Liver Disease Questionnaire—Non‐Alcoholic Fatty Liver Disease version instrument, a 75‐item‐long item selection questionnaire was administered to 25 patients with non‐alcoholic fatty liver disease. After item reduction, factor analysis found that 98.7% of variance in the remaining items would be explained by six factors. Thus, the resulting Chronic Liver Disease Questionnaire—Non‐Alcoholic Fatty Liver Disease version instrument had 36 items grouped into six domains: Abdominal Symptoms, Activity, Emotional, Fatigue, Systemic Symptoms, and Worry. The independent validation group included another 104 patients with non‐alcoholic fatty liver disease. The Cronbach's alphas of 0.74‐0.90 suggested good to excellent internal consistency of the domains. Furthermore, the presence of obesity and history of depression were discriminated best by Chronic Liver Disease Questionnaire—Non‐Alcoholic Fatty Liver Disease version scores ( P <.05). The domains' correlations with the most relevant domains of Short Form‐36 exceeded 0.70. Test‐retest reliability in a subgroup of patients (N=27) demonstrated no significant within‐patient variability with multiple administrations (all median differences were zero, all P >.15, intraclass correlations .76‐.88). Conclusion: The Chronic Liver Disease Questionnaire—Non‐Alcoholic Fatty Liver Disease version is a disease‐specific health‐related quality of life instrument developed and validated using an established methodology and useful for clinical trials of non‐alcoholic fatty liver disease.